The level of job satisfaction among nurses at the General ​Al-Iman General Hospital: Field study applied to a sample of nurses at ​Al-Iman General Hospital in Riyadh - AlRashidi, Khaled Sharia; Sumaida, Omar Ali Al- Sagheer (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed at identifying the level of job satisfaction among male and female nurses at Al- Iman General Hospital. The study also aimed at detecting the factors that have the most impact on the level of job satisfaction among male and female nurses (the study sample) such as (marital status, age, gender, monthly salary, social relations, educational level). The study also aimed t developing a suggested proposal to improve the level of job satisfaction among male and female nurses at Al- Iman General Hospital. The researcher used the social survey method to identify the study objectives. The study sample consisted of (115) workers of Al- Iman General Hospital in Riyadh, using the questionnaire as a tool to collect data. The collected data were processed through the SPSS program. In light of this data, the study indicated that there is a statistically significant relationship at the level 0.05 between the administrative factor and the psychological factor among male and female nurses as the correlation coefficient was (0.828) and the level of significance (0.00) that is less than 0.01. There is also a statistically significant relationship between the administrative factor, the training factor, and the remunerations and incentives factor among male and female nurses at Al- Iman General Hospital in Riyadh. The study also indicated that there were no statistically significant differences among the respondents regarding the level of satisfaction with all factors according to x of the marital status, educational qualification, professional- grade, and the number of years of service variables. In light of the results, the researcher presented the following recommendations: • Developing all aspects that improve the level of satisfaction among nurses, especially in the aspects where their level of satisfaction is low. This improvement shall be through intensive training courses and providing nurses with an opportunity to obtain external courses or training in some major hospitals • A training plan shall be organized to train all nurses, ensuring that training opportunities are for all employees. 3.The aspects that nurses have high satisfaction with such as psychological aspects and social relationships shall be preserved. • The hospital shall have a department, authorized to solve problems, that reduce the level of satisfaction among male and female nurses t Al- Iman General Hospital, and to develop appropriate ways to address these problems.